Good Governance dalam Pelayanan Publik - Jus Samuel Sihotang (Universitas 45 Surabaya, 2023)
Good governance implies that the administration of government institutions is carried out based on the interests of society and the prevailing norms. This study intends to describe good governance in public services. This research uses the library research method. Data collection is done through books, magazines, and articles that have been published in various scientific journals. The results of the discussion show that there are several solutions in implementing good governance, namely: establishing service standards, compiling Standard Operating Procedures (SOP), compiling customer satisfaction surveys, and developing a complaint handling system. In the future, it is hoped that the services provided through the idea of good governance will be more easily obtained, provide the best service to the community, and not be expensive. Adopt good governance practices, with the three pillars of civil society, government and business supporting and working together.